The effectiveness of plasmapheresis treatment in the patients with HELLP Syndrome and eclampsia in the intensive care unit - Merve Yazıcı Kara (Dicle Medical Journal, 2014)
Objective: In our study we aimed to state the effectiveness of plasmapheresis treatment in the patients with HELLP Syndrome and eclampsia in the intensive care unit. Methods: Patients who are with the diagnosis of HELLP Syndrome and eclampsia in our intensive care unit between the years of 2005-2010 were reviewed retrospectively. The patients’ characteristics, before and post-plasmapheresis biochemical and hematological values, urine outputs, APACHE II (Acute Physiology and Chronic Health Evaluation System), GCS, (Glasgow Coma Scoring), SOFA (Sequential Organ Failure Assessment) and MODS Scoring (Multiple Organ Dysfunction Score) are recorded. The effectiveness of plasmapheresis is evaluated. Results: 8 were HELLP Syndrome and 6 were eclampsia of 16 patients. The mean age was 29,5(±5,9). 2 of 6 eclampsia patients and, 1of 8 HELLP Syndrome patient were died. Age, APACHE II, MODS, GCS and the urine output are the significant clinical factors that determines the mortality (p<0.03). After the plasmapheresis therapy a significant improvement was seen in platelet and total protein numbers, MODS score, AST, GGT, LDH, lactate and creatinine levels. (p<0.03) Conclusion: Plasmapheresis treatment in the patients with HELLP Syndrome and eclampsia is a safe method and provides a significant development in biochemical values and patients’ clinics.